IONOSPHERIC DISTURBANCES OVER PRIMORSKY KRAI CAUSED BY THE ERUPTION OF THE HUNGA TONGA-HUNGA HA’APAI VOLCANO ON JANUARY 15, 2022 - М. А. Bolsunovskii; N. V. Shestakov; G. I. Dolgikh; N. P. Perevalova; А. S. Ten (Геодинамика и тектонофизика, 2024)
The explosive eruption of the Hunga Tonga-Hunga Haapai volcano occured on January 15, 2022 at 04:02 UTC led to generation of covolcanic ionospheric disturbances that spread over long distances. Using GNSS data obtained at permanent stations of the IGS network and sites located on the territory of Primorsky Krai, the search and analysis of ionospheric disturbances over the territory of Primorsky Krai and adjacent areas was performed. The velocity of the covolcanic ionospheric disturbances recorded over the Primorsky Krai reached about 340 m/s, and the average amplitude was equal to 1.0 TECU. The results obtained from GNSS-data were also compared with the results of observation data obtained by a laser strainmeters (oriented in the directions "north – south" and "east – west") and a laser nanobarograph located at the Schultz Cape (the south of Primorsky Krai). As a comparison result, time delays between the moments of fixation of disturbances in the troposphere and ionosphere were found. The delay between the first peaks of disturbances was equal to ~50 min.